The Effectiveness of Psychoreligious Intervention: Murottal Al-Quran on Pain and Stress Level of Bone Cancer Patient - Priyanto Priyanto; Achmad Fauzi Kamal; Debie Dahlia (Indonesian Journal of Global Health Research, 2020)
Psychoreligious intervention of murottal Al-Qur'an is a therapy given to patients by listening to verses of the Qur'an for a few minutes to have a positive impact on the patient's physiological and psychological condition, thereby providing a relaxing effect to reduce pain and stress level. The purpose of this study was to determine the effectiveness of psychoreligious intervention of murrotal Al-Quran on pain and stress level of bone cancer patients in Semarang Regency. This was a quasi-experimental study with pre and post-test through a control group design. The population of this study were patients with bone cancer who were undergoing outpatient care in Semarang Regency Hospital, living in the regency of Semarang. The sampling technique used was purposive sampling with the number of respondents obtained 36 patients. The data were collected through Numeric Rating Scale aiming to measure the pain scale and DASS 42 questionnaire consisting of 14 statements to measure the level of stress. The therapeutic action procedure of psychoreligious intervention of murrotal Al-Quran used Ar-Rahman letter for 20 minutes which was in accordance with standard operating procedures. The data were analyzed using t-test. The results showed that there was a significant difference of pain and stress level before and after the intervention. Psychoreligious intervention of murottal Al-Qur'an was effective in reducing pain level in bone cancer patients (p-value=0.001<α=0.05). Psychoreligious intervention of murottal Al-Qur'an can effectively reduce stress level of bone cancer patients (p-value=0.001<α=0.05). Psychoreligious intervention of murrotal Al-Quran can be used as a therapeutic modality to reduce the pain and stress level of bone cancer patients during home treatment period which brings positive impact to improve the patient's physiological and psychological well-being. This intervention will help the process of recovery of the patients from their cancer.